Creatine supplementation does not improve physical performance in a 150 m race - Javierre, C.; Lizarraga, M. A.; Ventura, J. L.; Garrido, E.; Segura, R. (Revista Española de Fisiología, 1997)
Creatine supplementation has been shown by several authors to improve physical performance in very high intensity, intermittent, exercises. The effect on performance, as well as in plasma creatine and lactate concentrations has been studied in a group of twelve sprinters of national class when running a distance of 150 m on two occasions, before and after creatine (or placebo) supplementation for the previous three days. The most important differences in the biochemical parameters analyzed have been in plasma creatinine concentration, which increased substantially both before and after the race in the group that had received a daily supplement of 25 grams of creatine monohydrate for the previous three days. Creatine supplementation, therefore, did not improve physical performance, in the conditions, when running a 150 m distance.